Comparing the Effectiveness of Encoding Techniques on Memory for Vocabulary in a Second Language. - Kim, Brian S.; Tran, Sophia H. N.; Fernandes, Myra A. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2025)
We compared the effectiveness of encoding techniques in learning a character-based language. During an encoding phase, participants naive to Korean were shown 40 English-Korean word pairs in Experiment 1 (80 in Experiment 2) and asked to either repeat aloud (produce) the Korean pronunciation or copy the image of the Korean character. Recognition was later assessed in two ways: On an auditory test, participants selected the correct pairing from two audio clips of Korean words, and on a visual test, they selected the correct pairing from among two visually presented Korean characters. In both experiments, copying Korean characters led to higher performance overall. Notably, we also found an interaction such that memory was higher on the auditory test when encoding required production and better on the visual test when encoding required copying. Results suggest that matching the encoding and retrieval test modality maximizes performance.